Exploring the gut microbiome: metaproteome analysis of HIV-exposed uninfected infants - Miller, Tara (Department of Integrative Biomedical Sciences (IBMS), 2025)
Background: HAART has decreased mother-to-child transmission, but it has introduced a new generation of HIV infected and unexposed infants (HEU) with unknown health implications. These infants have been observed to be more vulnerable to disease and have weaker immune responses. The gut microbiome plays a pivotal role in human health by aiding in metabolism, nutrient availability and immune development and function. The mucosal immune system and microbiome work in synergy to maintain host immunity and balance for optimal host health. Gut dysbiosis is linked to diseased states, with gut dysbiosis being well documented amongst HIV infected individuals. HEU infants' altered immunity and health could be linked to gut dysbiosis. Looking into the metaproteome of the infant gut to find any perturbations from healthy counterparts could give insight into their weakened states. Aim: To analyse the metaproteome of the infant gut to identify any alterations in a HIV exposed infant's gut, through analysis of the stool microbiome, accounting for their poor health. Design: Analysis of infant stool samples for the 1st week of life from a cohort comprised of HIV infected mothers and HIV uninfected mothers. Using data-independent acquisition mass spectrometry (SWATH) to identify human and microbiome proteins in samples using Evosep40-SPD and TTOF 6600. In-silico library in DIA-NN used for protein identification, followed by data clean up and pre-processing in R studio and excel. Analysis of the proteins carried out in R studio and Metaboanalyst 5.0. Results: Metaproteomic analysis method used allowed for deep metaproteome profiling and gives a greater understanding into the microbiome functioning than genomic analysis. The protein level Random Forest regression model analysis revealed HEU and HU clustering, in which both human and bacterial proteins are contributing. Infant proteins revealed alteration in MUC2 mucin gut barrier and inflammation in HEU infants, differences in immune proteins from breastmilk proteins, and bacterial proteins revealed Ruminococcus gnavus as an HEU associated species. Conclusion: The altered gut barrier paired with gut inflammation is strongly correlated with bacterial dysbiosis seen in HEU guts. The identified differential species, Ruminococcus gnavus, has been implicated in various diseased states in the gut (IBD and Crohn's), involved in autoimmune diseases (lupus) and neurological diseases (Parkinson's). This reveals the focus for future research to identify potential targets for therapeutic treatment to improve the health of these infants.